2012
DOI: 10.1002/ijc.27975
|View full text |Cite
|
Sign up to set email alerts
|

High expression of crystallin αB represents an independent molecular marker for unfavourable ovarian cancer patient outcome and impairs TRAIL‐ and cisplatin‐induced apoptosis in human ovarian cancer cells

Abstract: Dysregulated apoptotic pathways are regarded as major reasons for chemoresistance development as a particular challenge in ovarian cancer therapy. In search of molecular factors affecting human ovarian cancer cell apoptosis and, consequently, patient survival, we examined tumors of 103 platinum-/taxane-treated ovarian cancer patients by mRNA-array hybridization, qPCR, and immunohistochemistry. We identified high expression of crystallin aB (CRYAB), a proposed negative regulator of tumor necrosis factor-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 39 publications
5
33
0
Order By: Relevance
“…This observation is consistent with the antiapoptotic function of CryAB previously reported by others (13,15,22). A recent study by Volkmann et al (34) further showed that overexpression of CryAB protected against cisplatin-induced apoptosis in human ovarian cancer cells. CryAB has been shown to bind and sequester proapoptotic proteins, such as Bax (13,15).…”
Section: Discussionsupporting
confidence: 92%
“…This observation is consistent with the antiapoptotic function of CryAB previously reported by others (13,15,22). A recent study by Volkmann et al (34) further showed that overexpression of CryAB protected against cisplatin-induced apoptosis in human ovarian cancer cells. CryAB has been shown to bind and sequester proapoptotic proteins, such as Bax (13,15).…”
Section: Discussionsupporting
confidence: 92%
“…It binds directly to TP53 (Watanabe et al 2009 ;Liu et al 2007 ). In the canonical wnt-signalling pathway, αB-crystallin binds to the E-cadherin-β-catenin complex to maintain a membrane location for the complex ) Recent data suggest that αB-crystallin could regulate systemic expansion of IMCs through a cell-intrinsic mechanism (Dieterich et al 2013 ) Metastasis The direct involvement of αB-crystallin in the regulation of the cell cycle combined with the fact that the overexpression of αB-crystallin itself can complete the transformation process in immortalized human mammary epithelial cells (Moyano et al 2006 ) CRYAB is a marker of poor prognosis in cancer (Moyano et al 2006 ;Ivanov et al 2008 ) and its ability to prevent apoptosis contributes to the aggressiveness of these and other tumours (Goplen et al 2010 ;Volkmann et al 2012 ). CRYAB expression in breast cancer is regulated by both TP53 and Ets1 (Bosman et al 2010 ).…”
Section: Fig 172 αB-crystallin At the Crossroads Of Life And Its Romentioning
confidence: 97%
“…CRYAB expression in breast cancer is regulated by both TP53 and Ets1 (Bosman et al 2010 ). αB-crystallin is associated signifi cantly with ovarian (Volkmann et al 2012 ), glioblastoma (Goplen et al 2010 ) and hepatocellular carcinomas (Tang et al 2009 ). αB-crystallin in combination with HSPB2 promote tumour vascularization (Dimberg et al 2008 ) via a VEGF-A based mechanism (Kase et al 2010 ).…”
Section: Fig 172 αB-crystallin At the Crossroads Of Life And Its Romentioning
confidence: 98%
“…Consequently HspB5 can be considered as a biomarker in the diagnosis of breast cancers, especially in those with advanced grade (Ivanov et al 2008 ;Sitterding et al 2008 ;Tsang et al 2012 ). Similarly, high levels of HspB5 are associated with low survival rate in hepatocellular carcinoma (Huang et al 2013 ;Tang et al 2009 ), ovarian carcinoma (Volkmann et al 2013 ), clear cell renal cell carcinoma (Ho et al 2013 ) and head and neck squamous cell carcinoma (van de Schootbrugge et al 2013 ). In non-small-cell lung cancer only the nuclear and not the cytoplasmic localized HspB5 correlated with poor survival (Cherneva et al 2010 ).…”
Section: Hspb5 Expression In Cancersmentioning
confidence: 97%